Pengaruh Profesionalisme Aparatur Terhadap Kualitas Pelayanan Publik Bidang Administrasi Pemerintahan - Amin, Mohamad (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2020)
The purpose of this study was to determine the extent of the influence of professionalism of the apparatus on the quality of public services in the field of government administration at the Kairatu subdistrict office, West Seram district (Studies on the Waimital Village Community, Kairatu district). The method used in this research is descriptive method with a quantitative approach. The population of this research is 40 people. The results show that after identifying the research variables, it is known that the distribution of respondents' answers to all independent variables is quite varied, but on average they are in the good category. Meanwhile, the condition of public service quality that was perceived by respondents (service users / customers) was also in the good category, but training was not satisfactory. Partially, aspects of the professionalism of urban village officials have a positive and significant influence and have a contributive relationship to the quality of public services.